Evaluation of the performance of MALDI-TOF MS and DNA sequence analysis in the identification of mycobacteria species - İLKİ, ZEYNEP ARZU (TUBITAK SCIENTIFIC & TECHNICAL RESEARCH COUNCIL TURKEY, 2018)
Background/aim: Matrix-assisted laser desorption/ionization time-of-flight (MALDI-TOF) mass spectrometry is an alternative way of identifying mycobacteria via the analysis of biomolecules. It is being increasingly used in routine microbiology practice since it permits early, rapid, and cost-effective identification of pathogens of clinical importance. In this study, we aimed to evaluate the efficacy of phenotypic identification of mycobacteria by the MALDI-TOF MS MBT Mycobacteria Library (ML) 4.0 (Bruker, Daltonics) compared to standard sequence analysis. Materials and methods: A total of 155 Mycobacterium clinical and external quality control isolates, comprising nontuberculous mycobacteria (NTM) (n = 95) and the Mycobacterium tuberculosis complex (MTC) (n = 60), were included in the study. Results: Identification by MBT ML4.0 was correctly performed in 100% of MTC and in 91% of NTM isolates. All of the MTC isolates were correctly differentiated from NTM isolates. Conclusion: Based on our results, MBT ML4.0 may be used reliably to identify both NTM and MTC.
Keywords: MALDI-TOF MS; identification; Mycobacterium; Mycobacterium tuberculosis complex; nontuberculous mycobacteria; DESORPTION IONIZATION-TIME; FLIGHT MASS-SPECTROMETRY; SP NOV.; SUBSP ABSCESSUS; DISEASE; INFECTION; CULTURES; CHIMERA; RELAPSE; MEMBERS